The metformin in tuberous sclerosis (MiTS) study: A randomised double-blind placebo-controlled trial. (February 2021) - Amin, Sam; Mallick, Andrew A; Edwards, Hannah; Cortina-Borja, Mario; Laugharne, Matthew; Likeman, Marcus; O'Callaghan, Finbar J.K.
Abstract: Background: Tuberous Sclerosis Complex (TSC) is a genetic disorder characterised by the development of benign tumours secondary to loss of inhibitory regulation of the mTOR (m echanistic T arget o f R apamycin) intracellular growth pathway. Metformin inhibits the mTOR pathway. We investigated whether metformin would reduce growth of hamartomas associated with tuberous sclerosis complex. Methods: In this multicentre randomized, double-blind, placebo-controlled trial, patients with a clinical diagnosis of tuberous sclerosis, aged over 10 years and with at least one renal angiomyolipoma of greater than 1 cm in diameter were enrolled. Participants were randomly allocated (1:1) by a secure website to receive metformin or placebo for 12 months. The primary outcome was percentage volume change of renal angiomyolipomas (AML) at 12 months compared to baseline. Secondary outcomes were percentage change at 12 months from baseline in volume of cerebral Subependymal Giant Cell Astrocytomas (SEGA); appearance of facial and ungual hamartomas; frequency of epileptic seizures; and adaptive behaviour. The trial is registered with The International Standard Randomised Controlled Trial Number (ISRCTN), number 92545532, and the European Union Drug Regulating Authorities Clinical Trials (EUDRACT), number 2011-001319-30. Findings: Between 1 November 2012 and 30 September 2015 72 patients were screened and 55 were randomly assigned to metformin (28) or placebo (27). Four participants withdrew between randomisation and starting treatment. All 51 patients who started therapy completed the trial and were assessed for outcome at 12 months. The median percentage change in angiomyolipoma (AML) volume was +7.6% (IQR -1.8% to +42.6%) for the placebo group and +8.9% (IQR 1.3% to 19.5%) for the metformin group ( p = 0.28). Twenty-seven patients had SEGAs: 13 received placebo and 14 metformin. The median percentage change in SEGA volume was +3.0% (IQR -22.8% to +27.7%) for the placebo group and – 20.8% (IQR – 47.1% to - 5.0%) for the metformin group ( p = 0.03). Twenty-one patients were assessed for seizure frequency: 9 received placebo and 12 received metformin. In the metformin group, a mean reduction of 43.7% from baseline in seizures was observed and in the placebo group a 3.1% mean reduction was observed, with a difference in response of 40.6% (95% CI -3.1% to +84.2%, p = 0.03). There were no significant differences between metformin and placebo groups for the other secondary outcomes. There were no deaths. Three serious adverse events (SAEs) occurred during the trial (all patients on metformin). Interpretation: Metformin did not reduce AML volume. Metformin did reduce SEGA volume and seizure frequency compared with placebo. There may be a role for metformin in slowing or reversing growth of some life-threatening hamartomas in TSC and for reducing seizure frequency. Further study is justified. Funding: This study was funded by the National Institute for Health and Research (NIHR) through the The Research for Patient Benefit Programme (RfPB).